Premiere Pro CC 2015 in-depth (John Wiley & Sons, 2014)
"Master Premiere Pro CC on your terms with this one-of-a-kind video training course. Adobe Premiere Pro CC puts the power of popular film and video editing software into the hands of hobbyists, students, and budding creative professionals, and Premiere Pro CC is packed with tools to help you edit video like a pro. Our instructors provide expert, straight-forward, user-friendly training to help you tackle Premiere Pro CC the way you want to learn. Dive deep into Premiere Pro's editing tools and learn techniques to enhance your video project Add transitions, graphics, credits, audio, and animation Use Premiere Pro's advanced editing tools including Scope, Audition, and Warp Stabilizer. If you're looking for real-world Premiere Pro CC instruction, you'll find it here."--Resource description page.